Data Processing in Multiport-Based Reflectometer System - Dvorak, Radek; Urbanec, Tomas (Společnost pro radioelektronické inženýrství, 2011)
The paper describes operations with DC output voltage of multiport based system. Proposed system is based on the same principle as common six ports systems, however the used coupler has more outputs. This allows extension of bandwidth and higher precision of the measurement. To process measured data standard six port system calculations are used. To get more accurate results than in the case of simple six port system additional statistical methods can be used. The higher number of outputs produces large amount of measurement and calibration data, however using described technique this amount of data were reduced.
Keywords: Six-port reflectometer; vector scattering parameters measurement; microwave detector; diode detector